2013
DOI: 10.1111/1556-4029.12205
|View full text |Cite
|
Sign up to set email alerts
|

Possible Fatal Acetaminophen Intoxication with Atypical Clinical Presentation

Abstract: Acetaminophen or paracetamol, a commonly used over-the-counter analgesic, is known to elicit severe adverse reactions when taken in overdose, chronically at therapeutic dosage or, sporadically, following single assumptions of a therapeutic dose. Damage patterns including liver damage and, rarely, acute tubular necrosis or a fixed drug exanthema. We present a case of fatal acetaminophen toxicity with postmortem blood concentration 78 μg/mL and unusual clinical features, including a visually striking and massive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…High-dose APAP-induced clinical intoxication is predominantly found in liver and renal cells; therefore, the majority of previous studies have focussed on the mechanisms underlying high-dose APAP-triggered liver and renal injury ( 17 , 37 , 38 ). Furthermore, certain studies have indicated that APAP can exhibit antitumor activities in certain tumor types, including breast cancer, liver cancer and neuroblastoma ( 26 , 39 – 43 ).…”
Section: Introductionmentioning
confidence: 99%
“…High-dose APAP-induced clinical intoxication is predominantly found in liver and renal cells; therefore, the majority of previous studies have focussed on the mechanisms underlying high-dose APAP-triggered liver and renal injury ( 17 , 37 , 38 ). Furthermore, certain studies have indicated that APAP can exhibit antitumor activities in certain tumor types, including breast cancer, liver cancer and neuroblastoma ( 26 , 39 – 43 ).…”
Section: Introductionmentioning
confidence: 99%
“…Among all patients with APAP intoxication, the prevalence rate of APAP-related renal function impairment has been estimated at <2% of all patients. 6 Most cases (53%) coexist with hepatic failure and acute kidney injury (AKI). Other cases of renal toxicity have mild liver involvement or no hepatic toxicity features.…”
Section: Introductionmentioning
confidence: 99%
“…While paracetamol is described as relatively nontoxic in therapeutic doses, it can be toxic when taken in a single or repeated high dose, or after chronic ingestion. Adverse effects typically associated with paracetamol intoxication are include acute liver failure, renal tubular necrosis and hypoglycemic coma (De Giorgio et al, 2013, Lancaster et al, 2015. According to recent information provided by the American National Poison Data System (NPDS), paracetamol is one of the 25 drugs associated with the largest number of fatalities, either alone or in combination with other medications (Mowry et al, 2015).…”
mentioning
confidence: 99%